Visualizing climate change: an exploratory study of the effectiveness of artistic information visualizations. Issue 1 (2nd January 2021) - Hahn, Ulrike; Berkers, Pauwke
Abstract : Artists creatively use scientific data in artistic information visualizations (AIVs) to address climate change. Yet, it is unclear how effective they are in making viewers consider climate change as important. To assess their reception, this research studies and compares AIVs in relation to four additional visual forms, which are common in the communication of climate change (information visualizations, news photos, digital art visuals and cartoons). Qualitative research consisting of a short survey, q-sort and semi-structured interviews was employed. Some AIVs were judged clearer and more agreed with than other AIVs, suggesting that a less abstract AIV style might be more suitable. In comparison to the other visual forms, the artistic information visualizations were the least effective in making viewers consider climate change as important. It appears that artists' free choice of data focus and artistic styles faces limits when depicting a complex topic such as climate change. A need for clarity or accompanying descriptions to the visualizations, at least when targeted at the general public without art training, might be necessary. The study did not show distrust in art's involvement in the climate change discourse.